US Literature and Italian Culture: A Long Romance (1763-1980) - Giorcelli, Cristina (Review of International American Studies, 2017)
Cristina Giorcelli University of Rome III Italy US Literature and Italian Culture: A Long Romance (1763-1980) This paper attempts to point out the powerful insights and the spirit of adventure of the US literature in the Italian culture, that were sometimes manifested by Italian critics and publishers alike, from (roughly) the end of the eighteenth century to the end of the twentieth century. Today, the great US literary masterpieces are, by and large, part of the Italian heritage, as indicated by the many translations, scholarly books and intelligent, innovative essays that keep being produced and published.